Osteoblasts are inherently programmed to repel sensory innervation - Leitão, L (2020)
Tissue innervation is a complex process controlled by the expression profile of signaling molecules secreted by tissue-resident cells that dictate the growth and guidance of axons. Sensory innervation is part of the neuronal network of the bone tissue with a defined spatiotemporal occurrence during bone development. Yet, the current understanding of the mechanisms regulating the map of sensory innervation in the bone tissue is still limited. Here, we demonstrated that differentiation of human mesenchymal stem cells to osteoblasts leads to a marked impairment of their ability to promote axonal growth, evidenced under sensory neurons and osteoblastic-lineage cells crosstalk. The mechanisms by which osteoblast lineage cells provide this nonpermissive environment for axons include paracrine-induced repulsion and loss of neurotrophic factors expression. We identified a drastic reduction of NGF and BDNF production and stimulation of Sema3A, Wnt4, and Shh expression culminating at late stage of OB differentiation. We noted a correlation between Shh expression profile, OB differentiation stages, and OB-mediated axonal repulsion. Blockade of Shh activity and signaling reversed the repulsive action of osteoblasts on sensory axons. Finally, to strengthen our model, we localized the expression of Shh by osteoblasts in bone tissue. Overall, our findings provide evidence that the signaling profile associated with osteoblast phenotype differentiating program can regulate the patterning of sensory innervation, and highlight osteoblast-derived Shh as an essential player in this cue-induced regulation.